Penataan Kawasan Wisata Curug Banyu Nibo Desa Sendangsari Kecamatan Pajangan Kabupaten Bantul Daerah Istimewa Yogyakarta - Amos Setiadi; Lucia Asdra Rudwiarti (Universitas Katolik Soegijapranata, 2020)
“Pengabdian pada Masyarakat” (Abdimas) of Curug Banyu Nibo was done to assist partner by designing tourism supporting facilities. The intended outcomes of this Abdimas are the increase of tourist visits and its effect on the welfare of the surrounding local communities. The Abdimas was conducted in three steps, i.e. Preparation and Data Collection; Location Survey and Interviewing Partners; Drafting Concepts and Designs. The conclusion of the program is a design of tourism supporting facilities in Curug Banyu Nibo such as gate, joglo, parks, pathways, gazebos, and culinary stalls.